(untitled) (Global Journal of Science Frontier Research, 2017)
Mineral exploration and processing have caused varying degree of environmental damage in Nigeria. These include alteration of ecological state, air, water, soil pollution, destruction of soil flora and fauna, loss of vegetation, landscape degradation and radiation emission. Since mineral exploration is still at the developmental state and in the hands of artisanal miners in most developing nations, the environmental impact of their ill-fated activities is inevitable. For a robust, sustainable eco-mining to be achieved, government agencies, environmentalist and industrial prospectors must take sound precautionary measures in remedying polluted sites and limiting re-introduction of hazardous material into the environment.